Metode Pembelajaran Kepemimpinan Rasulullah SAW Kepada Para Sahabat dalam Kitab Sunan Ibn Majah - Qutub, Sayid; Hafidhuddin, Didin; Mujahidin, Endin (Ta’dibuna: Jurnal Pendidikan Islam, 2016)
The Government of the Republic of Indonesia and experts have provided leadership requirements are very strict agency also has a good learning method, a lot of achievements have earned, but why are there still negative cases in this country? The problem under study is about leadership learning methods are to be used Rasulullah SAW to the companions in the book Sunan Ibn Majah, and how to implement the teaching methods in educational leadership at the institution? The learning method is the means used to implement a plan that has been prepared in the form of real and practical activities to achieve the learning objectives. Leadership is the behavior of an individual who leads the activities of a group to a common goal to be achieved (shared goal). Companions are receiving direct hadith from the Prophet Muhammad SAW both subjects and nature answers to the problems faced. This study uses literature review are sourced from the literature. Researchers collected data based on that described for the qualitative analysis. This study addressed the issue of leadership learning methods that take hadith as its foundation. While to analyze the problem, researchers classified the hadith based on the theory of learning methods and leadership to further analyze the classification results and relate it to the subject. Through this study found that the leadership of the Prophet Muhammad learning methods.The most widely used Prophet S.A.W. is exemplary method, lecture and question and answer method. Prophet S.A.W. also use a unifying method, method the direction giver, liability method, the method of advice, wills method, the method fun, istikharah methods, and methods of Tahajjud, as well as commonly used method is the method of the story, the assignment method, the method of teaching leadership in educating fellow companions. This study obtained data that the term leadership (Imamate term) the most widely applied is obedient to the priest. Then the value of leadership exercised by the Prophet Muhammad the companions of the most widely applied is exemplary. The researcher recommends that the leadership institute master three methods above, the exemplary method, a lecture and subsequent question and answer method of applying the values of exemplary leadership, piety to Allah SWT, and noble character in leadership at the institution. Keywords: leadership, learning method, sahabah, Sunan Ibnu Majah